The relationship between arterial stiffness index and coronary heart disease and its severity - Longjian Gao (BMC, 2021)
Abstract Background Arterial stiffness index (ASI) is closely related to coronary atherosclerosis. This study aims to explore whether ASI can predict coronary heart disease (CHD) and its severity. Methods In this study, a total of 726 patients with suspected CHD were recruited. Based on coronary angiography results, the subjects were assigned into three groups: the control group (without obvious coronary artery disease), single-vessel disease group, and multi-vessel disease group (the number of vessels diseased ≥ 2). At the same time, according to the results of angiography, myocardial enzyme spectrum, electrocardiogram, color Doppler echocardiography and clinical manifestations, these patients were divided into four groups: the control group, stable angina (SA) Group, unstable angina (UA) group, and acute myocardial infarction (AMI) group. We have compared whether there were differences in ASI and related baseline data between groups. Receiver operating curve (ROC) analysis was conducted to determine whether ASI could predict CHD and evaluate the severity. Results ASI was positively correlated with the number of diseased branches of coronary artery. The value of ASI was increased as the number of the diseased branches increased. The ASI value in the SA group was significantly higher compared with the control group. Furthermore, the ASI value in the UA and AMI groups was remarkably increased compared with the control and SA groups. The results of ROC analysis indicated that the sensitivity and specificity of ASI was 71.0% and 85.4% in diagnosing CHD, respectively. While ASI was used in predicting the severity of CHD, the sensitivity was 72.1% and specificity 57.9%. Conclusion ASI is of great value in the diagnosis of coronary heart disease and the prediction of its severity.